Polymer Basics - Wilson Andrew; Gwynne Jessica; DoITPoMS, University of Cambridge
Este conjunto de animaciones brinda una introduccin̤ a los conceptos bs̀icos de la ciencia de polm̕eros. Incluye estructura molecular, sn̕tesis y ensayos de identificacin̤. Est ̀comprendido por los siguientes elementos:3D rotatable structures of 9 polymers Newman projections and change in potential energy with torsion angle for butane 3D rotatable structure of polythene Estimating the size of a polymer Random walk simulation Polymerisation mechanisms Identification tests for polymers